Pengaruh Reskilling–Upskilling Dan Human–Ai Collaboration Terhadap Employee Well-Being Pada PT Nielseniq Palembang - Siti Mujriyah; Mohammad Kurniawan DP; Try Wulandari (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
This study aims to analyze the effect of Reskilling-Upskilling and Human-AI Collaboration on Employee Well-Being at PT NielsenIQ Palembang. This study uses a quantitative approach with a saturated sample technique on 60 respondents. Data analysis was carried out using multiple linear regression with the help of SPSS version 27. The results of the study show the following regression equation: Y = 0.520 + 0.530X₁ + 0.491X₂. Partially, Reskilling-Upskilling (X₁) has a positive and significant effect on Employee Well-Being with a calculated t value of 4.262> t table 2.002 and a significance value of 0.000 <0.05. Human AI Collaboration (X₂) also has a positive and significant effect on Employee Well-Being with a calculated t value of 4.109> 2.002 and a significance value of 0.000 <0.05. Simultaneously, Reskilling-Upskilling and Human -AI Collaboration significantly influence Employee Well-Being, with a calculated F-value of 32.239 > F-table 3.16 and a significance value of 0.000 < 0.05. The Adjusted R-Square value of 0.514 indicates that 51.4% of the variation in Employee Well-Being can be explained by Reskilling-Upskilling and Human -AI Collaboration, while 48.6% is influenced by other variables outside this study. Therefore, Reskilling-Upskilling and Human AI Collaboration are statistically proven to have a positive and significant effect on Employee Well-Being of PT NielsenIQ Palembang employees.